Effectiveness of the therapeutic laser in the syndrome of dysfunction of the temporomandibular joint of arthrogenic origin = Eficacia del láser terapéutico en el síndrome de disfunciónde la articulación temporomandibular de origen artrogénico - Castillo Madrigal, Josué
Temporomandibular joint dysfunction syndrome (TMD), is a collective term characterized by symptoms involving chewing muscles, temporomandibular joint and orofacial structures. The efficacy of low intensity laser (LLLT) Gallium arsenide, in combination with a non-steroidal anti-inflammatory drug (NSAID) was evaluated. The main objective was to evaluate the maximum mouth opening without pain (ABM), arthralgia in the joint capsule through visual analog scale (VAS), laterality, protrusion, joint noises and count of tablets ingested per group. A controlled clinical trial (double-blind-randomized) was carried out in 30 subjects, who presented DTM of arthrogenic etiology; 5 applications of LLLT were made with wavelength of 810 nm, output optical power of 100-200 mw, emission PW=Pulsed (1-10,000Hz), dose of 10 jouls-cm², time of 1.44 minutes in mouth closed and with the mouth half open. One more follow-up appointment per month. There were two groups: experimental and control group, where different variables were analyzed (ABM, laterality, protrusion, VAS and sociodemographic). In the control group, a supposed LT application (not active) was made, for later comparison. Pain-free ABM was assessed in all appointments in addition to the other clinical parameters. Repeated measures analysis was performed with mixed models. Thirty patients were included of which 28 finished the treatment, two of them were lost during follow-up. The groups were similar in all their baseline variables. There were no statistically significant differences when applying the final multiple regression analysis, in the ABM, or in any other of the clinical parameters analyzed. LT was not effective in treating arthrogenic DTM.